Kesejahteraan Spiritual pada Mahasiswa Penghafal Al-Qur’an - Widwi Mukhabibah; Retno Hanggarani Ninin; Poeti Joefiani (Jurnal Studia Insania, 2017)
Nowadays, memorizing the Qur'an is growing and interested in children to adults, including college students. The activity is interesting because in the perspective of Islamic Shari'ah, memorizing the Qur'an is not an obligation. Therefore, in psychological science, it will be useful to find any factors that encourage students to do so. An initial survey found that students had belief associated with the spiritual domain of divinity and felt calm when memorizing the Qur’an. Those factors will be studied in the concept of spiritual well-being by Ellison (1983). This quantitative study was conducted on students at Universitas Padjadjaran. There were 40 students selected with snowball sampling. The result showed that as many as 85% of students had high spiritual well-being. It showed that the majority of students have a harmonious and stable life indicated by the closeness with Allah SWT and life satisfaction.